(untitled) (Web of Teachers: Inderscience Research, 2025)
Activities are the various ways in which these methods can be put into practice, whilst teaching methods are the more general strategies utilized to assist students in meeting learning objectives. Instructional strategies benefit pupils in the following way: -grasp the course material and learn how to use it in certain situations. Teachers need to choose which instructional strategies will best serve a certain learning objective. This alignment is necessary for it to be effective. An instructor should take learning outcomes, student needs, and the learning environment into account while making the best decision.